2018
DOI: 10.1002/adom.201701162
|View full text |Cite
|
Sign up to set email alerts
|

White‐Light Generation through Nonlinear Optical Response of 1,3,5,7‐Tetraphenyladamantane: Amorphous versus Crystalline States

Abstract: The development of advanced nonlinear media as well as active optical materials for light conversion applications is an ongoing process. [1,2] Aims include improved conversion efficiencies, brilliance, i.e., beam quality, and accessible target wavelengths. Light-converting materials for white-light generation are of particular interest, e.g., for white light-emitting diodes (LEDs) and their applications. Here, phosphors offer great efficiency even at low driving power densities and huge spectral versatility ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 26 publications
(24 reference statements)
0
26
0
Order By: Relevance
“…Indeed, single-crystals of compound 17 showed SHG, while an amorphous sample generated white light (Figure 9, left). [13] Inspection of the power dependence of the WLG in 17 demonstrated that lower laser power shifts the spectrum to lower energies, as also found for 1. Furthermore, a weak SHG signal is detected at low pump energies (Figure 9, right).…”
Section: Materials Investigationsmentioning
confidence: 56%
See 1 more Smart Citation
“…Indeed, single-crystals of compound 17 showed SHG, while an amorphous sample generated white light (Figure 9, left). [13] Inspection of the power dependence of the WLG in 17 demonstrated that lower laser power shifts the spectrum to lower energies, as also found for 1. Furthermore, a weak SHG signal is detected at low pump energies (Figure 9, right).…”
Section: Materials Investigationsmentioning
confidence: 56%
“…Habitus [a] Optical response Remarks [(StySn) 4 S 6 ] (1) [8] a WLG Sty = styryl [(PhSn) 4 S 6 ] (2) [12] a WLG [(MeSn) 4 S 6 ] (3) [12] a SHG [(NpSn) 4 S 6 ] (4) [12] a SHG Beginning order, π stacking [(BnSn) 4 S 6 ] (5) [10] c SHG [(R 1 Sn) 4 S 6 ] (6) [10] a WLG R 1 = (CH 2 ) 2 À (C 6 H 4 )CO 2 Et [(η 1 -CpSn) 4 S 6 ] (7) [10] a WLG [(CySn) 4 S 6 ] (8) [10] a WLG [(PhSn) 4 Se 6 ] (9) [10] a WLG [(BnSn) 4 Se 6 ] (10) [10] c WLG Melts upon irradiation [(R 1 Sn) 4 Se 6 ] (11) [10] a WLG R 1 = (CH 2 ) 2 À (C 6 H 4 )CO 2 Et [(η 1 -CpSn) 4 Se 6 ] (12) [10] a WLG [(CySn) 4 Se 6 ] (13) [10] a WLG [(PhGe) 4 S 6 ] (14) [12] a WLG [(PhSi) 4 S 6 ] (15) [9] c SHG [(NpSi) 4 S 6 ] (16) [9] c None Decomposition 1,3,5,7-Tetraphenyl-adamantane (17) [13] a WLG Nearly insoluble material [34] c SHG [{(Me 3 P) 3 AuSn}(PhSn) 3 S 6 ] (18) [11] c WLG Amorphization upon laser irradiation [{(Et 3 P) 3 AgSn}(PhSn) 3 S 6 ] (19) [11] c WLG Amorphization upon laser irradiation [{(Me 3 P) 3 CuSn}(PhSn) 3 S 6 ] (20) [11] c None WLG hindered by re-absorption…”
Section: Compoundmentioning
confidence: 99%
“…5). 83 Further studies showed that this effect seems to be specic to adamantane-type organotetrel clusters and to organic adamantanes, 84 given that the samples are amorphous and possess cyclic organic substituents. 85,86 This represents the current state of knowledge, as the exact mechanism for this process is still unknown and under investigation.…”
Section: Organotin Chalcogenide Clusters and Related Compoundsmentioning
confidence: 99%
“…Recently, a new class of materials has been synthesized which exhibits unique non-linear optical properties. Some of these substances convert infrared light from a commercially available low-cost low-power laser diode into brilliant white light, thereby maintaining the favourable coherent emission characteristics of the laser [1][2][3][4][5]. This so-called supercontinuum generation was so far only possible if expensive high-power pulsed laser sources were used, and was therefore mainly restricted to academic applications [6][7][8].…”
Section: Introductionmentioning
confidence: 99%